(untitled) (International conference on multidisciplinary science, 2025)
This article examines the peculiarities and challenges of adapting foreign educational experiences to national education systems. The study analyzes the theoretical foundations of educational borrowing, explores successful cases of adaptation from various countries, and identifies key factors that influence the effectiveness of implementing foreign practices in local contexts. The research emphasizes the importance of considering cultural, socio-economic, and institutional factors when transferring educational innovations. The article proposes a framework for systematic adaptation that balances international best practices with national educational priorities and traditions. The findings suggest that successful adaptation requires careful contextualization, stakeholder engagement, and gradual implementation rather than direct transplantation of foreign models.